Analysis of 20-Year Trends in Medicare Reimbursement for Reconstructive Microsurgery - Teven, Chad M.; Gupta, Nikita; Yu, Jason W.; Abujbarah, Sami; Chow, Nathan A.; Casey, William J., III; Rebecca, Alanna M. (Journal of Reconstructive Microsurgery, 2021)
Background Microsurgery is being increasingly utilized across surgical specialties, including plastic surgery. Microsurgical techniques require greater time and financial investment compared with traditional methods. This study aimed to evaluate 20-year trends in Medicare reimbursement and utilization for commonly billed reconstructive microsurgery procedures from 2000 to 2019.Methods Microsurgical procedures commonly billed by plastic surgeons were identified. Reimbursement data were extracted from The Physician Fee Schedule Look-Up Tool from the Centers for Medicare and Medicaid Services for each current procedural terminology (CPT) code. All monetary data were adjusted for inflation to 2019 U.S. dollars. The average annual and total percentage changes in reimbursement were calculated based on these adjusted trends. To assess utilization trends, CMS physician/supplier procedure summary files were queried for the number of procedures billed by plastic surgeons from 2010 to 2018.Results After adjusting for inflation, the average reimbursement for all procedures decreased by 26.92% from 2000 to 2019. The greatest mean decrease was observed in CPT 20969 free osteocutaneous flaps with microvascular anastomosis (−36.93%). The smallest mean decrease was observed in repair of blood vessels with vein graft (−9.28%). None of the included procedures saw an increase in reimbursement rate over the study period. From 2000 to 2019, the adjusted reimbursement rate for all procedures decreased by an average of 1.35% annually. Meanwhile, the number of services billed to Medicare by plastic surgeons across the included CPT codes increased by 42.17% from 2010 to 2018.Conclusion This is the first study evaluating 20-year trends in inflation-adjusted Medicare reimbursement and utilization in reconstructive microsurgery. Reimbursement for all included procedures decreased over 20% during the study period, while number of services increased. Increased consideration of these trends will be important for U.S. policymakers, hospitals, and surgeons to assure continued access and reconstructive options for patients.
Keywords: finance; health policy; insurance; Medicare; microsurgery; reimbursement